2019
DOI: 10.1111/imj.14069
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endovascular thrombectomy with and without bridging thrombolysis for acute large vessel occlusion ischaemic stroke

Abstract: Our study supports the current practice of administering intravenous alteplase before endovascular therapy. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
(64 reference statements)
1
26
2
Order By: Relevance
“…Moreover, patients treated with combined therapy had significantly lower rates of death/severe disability as compared with patients undergoing only MT. These results are consistent with those reported from observational studies 913,35,36 and available meta-analyses. 26,27 A recent post hoc analysis of the ASTER trial (Contact Aspiration Versus Stent Retriever for Successful Revascularization) showed a lower 90-day mortality rate in the IVT+MT group than after MT alone, and a better functional outcome, recanalization rate, and reduced mortality in a subgroup of patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, patients treated with combined therapy had significantly lower rates of death/severe disability as compared with patients undergoing only MT. These results are consistent with those reported from observational studies 913,35,36 and available meta-analyses. 26,27 A recent post hoc analysis of the ASTER trial (Contact Aspiration Versus Stent Retriever for Successful Revascularization) showed a lower 90-day mortality rate in the IVT+MT group than after MT alone, and a better functional outcome, recanalization rate, and reduced mortality in a subgroup of patients.…”
Section: Discussionsupporting
confidence: 93%
“…Observational retrospective analyses gave conflicting results: while some of them suggested a benefit of IVT pretreatment, [9][10][11][12][13] in terms of higher rate of recanalization, shorter duration of the endovascular procedure, lower number of passes of the thrombectomy device per patient, or better clinical outcome, others did not find significant differences between the two approaches. [14][15][16][17][18][19][20][21][22] A pooled analysis 23 of the STAR 24 and SWIFT 25 trials suggested that treatment with IVT before MT does not add any clinical benefit as compared to MT alone.…”
Section: Introductionmentioning
confidence: 99%
“…IVT is associated with improved recanalization rates. This can be explained by the pharmacologic mechanism: the clot is dissolved from the outer edge and can therefore be accessed by the mechanical device easier [22]. Another explanation could be, that small fragments of the initial thrombus are dissolved during the intervention and do not occlude distal branches.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor: Stroke is a sudden attack of disturbance of cerebral blood circulation; its incidence is getting higher and higher, and it has become the second most common cause of death, the fourth leading cause of loss of productivity, and the main cause of disability of people all over the world, [ 1 , 2 ] which has caused very serious pressure and burden on the social economy and public health. Although intravenous thrombolysis (IVT) with alteplase has been recognized as the first scheme for acute ischemic stroke within 4.5 h of onset, [ 3 , 4 ] there are still many patients who do not benefit from it and it lead to serious complications. Nowadays, endovascular thrombectomy (EVT) for acute ischemic stroke has also become a part of the standard treatment for patients with acute ischemic stroke complicated with large-vessel occlusion.…”
mentioning
confidence: 99%
“…Many epidemiological studies have shown that patients have no significant benefit from bridging endovascular thrombectomy compared with direct EVT (dEVT), [ 4 ] while other studies have shown the opposite results. [ 3 ]…”
mentioning
confidence: 99%